2016
DOI: 10.1039/c5nr09003b
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced near-infrared photoresponse of organic phototransistors based on single-component donor–acceptor conjugated polymer nanowires

Abstract: Single-component near-infrared phototransistors based on ambipolar organic semiconductor nanowires have been investigated and compared with their corresponding thin-film counterparts. The nanowire organic phototransistors (NW-OPTs) showed photocurrent/dark-current ratios and photoresponsivities as high as 1.3 × 10(4) and 440 mA W(-1) for the p-type channel, and 3.3 × 10(4) and 70 mA W(-1) for the n-type channel, respectively, upon near-infrared illumination with an intensity of 47.1 mW cm(-2). These were much … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 47 publications
(58 reference statements)
2
52
0
Order By: Relevance
“…For instance, along the crystalline texture orientation after annealing treatment in Chen's work, BODIPY‐BF2 film‐based NIR OPTs showed remarkable photoresponsivity ( R ) of 1.14 × 10 4 A W −1 under an 850 nm laser, which is two orders of magnitude greater than the amorphous film . Qiu and co‐workers reported that the NIR photoresponsivity of PBIBDF‐TT transistors was enhanced by replacing the thin‐film with 1D nanowire (NW) structures . Nevertheless, few reports remain about the restriction of dark current in NIR OPTs, which would worsen the sensitivity, particularly in low bandgap semiconductors .…”
Section: Comparison Of Figure Of Merit Of Nir Phototransistor Based Omentioning
confidence: 99%
“…For instance, along the crystalline texture orientation after annealing treatment in Chen's work, BODIPY‐BF2 film‐based NIR OPTs showed remarkable photoresponsivity ( R ) of 1.14 × 10 4 A W −1 under an 850 nm laser, which is two orders of magnitude greater than the amorphous film . Qiu and co‐workers reported that the NIR photoresponsivity of PBIBDF‐TT transistors was enhanced by replacing the thin‐film with 1D nanowire (NW) structures . Nevertheless, few reports remain about the restriction of dark current in NIR OPTs, which would worsen the sensitivity, particularly in low bandgap semiconductors .…”
Section: Comparison Of Figure Of Merit Of Nir Phototransistor Based Omentioning
confidence: 99%
“…Phototransistors based on ambipolar materials, which are single component systems that can function as both p-and n-type semiconductors, have also been demonstrated. [24][25][26][27] Single component, ambipolar transistors are cost-effective and boast several advantages including largearea applicability and simple fabrication. Despite their advantages, research on ambipolar material-based phototransistors is insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…When the gate bias is above the threshold (on‐state), the barrier becomes smaller, which facilitates the drift of photogenerated carriers thus gaining larger drain current (panel IV of Figure b). However, as the gate bias keeps increasing, the photocurrent gradually saturates and decreases slightly, which could be explained by the enhanced photoexcited carrier recombination at high carrier concentrations …”
Section: Resultsmentioning
confidence: 99%